Health Related Quality of Life of Children with Congenital Heart Disease Attending at Tertiary Level Hospital - Mishra, Tulashi Adhikari; Sharma, Pratima (Journal of Nepal Health Research Council, 2019)
Background: Congenital heart disease is one of the common congenital anomaly among the children affecting growth and development of the child and increasing susceptibility of the child to failure to thrive. The objective of the study is to find out the overall health related quality of life of children with congenital heart disease.Methods: A descriptive cross sectional study was carried out among 150 children with congenital heart disease attending in the pediatric out-patient department of Shahid Gangalal National Heart Centre, Bansbari, Kathmandu. The data was collected within the period of 2017/07/16 to 2017/08/16 using purposive sampling technique. Data was collected through interview technique using semi structured questionnaire. Collected data were entered in Statistical Package for Social Science 16 version and analyzed by using descriptive and inferential statistics.Results: The study findings revealed that more than half (52.7%) of the children had satisfactory overall health related quality of life. Health related quality of life is significantly associated with age group of the child (p=0.018), and education of mother (p=0.017)).Conclusions: It can be concluded that more than half of the children tends to have satisfactory overall health related quality of life.Ventricular septal defect is the commonest congenital heart disease. The health related quality of life of children with congenital heart disease tends to be better among those with educated mother and increasing age of the children. Therefore, awareness raising of mothers related to disease condition and care of children with congenital heart disease through mass media or proper intervention program might help to promote the quality of life of children with congenital heart disease. Keywords: Congenital heart disease; health related quality of life.